Representation of Black People in Dahmer - Monster: The Jeffrey Dahmer Story - Daniela, Lerissa; Kusumaningtyas, Purwanti (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
This study examined the representation of color-based injustice in Dahmer – Monster: The Jeffrey Dahmer Story series shown on Netflix in September 2020. This series told about a serial killer to 17 men murdered and mutilated by Jeffrey Dahmer which happened in late 1980s until 1991 in Milwaukee, United States of America. 16 out of the 17 victims were black people, while Dahmer himself was a white man. Multimodal Discourse Analysis (MDA) theory, specifically the three metafunction framework by Kress and van Leeuwen (2021) was used to analyze the semiotic resources presented in Dahmer series, including dialogues, visual images, and gestures, to understand how these resources were interrelated in constructing the representation of black people in that series. Data was taken from the 10 episodes of the series. This research found four themes of black people representation. First was the stereotypical portrait of blacks as the poor and less educated than the sufficient whites. Second was the portrayal of discriminative treatment toward black people that strongly shown in the series. Third was how the colored people responded to the discrimination by speaking up for their rights. The series magnified the significance of the blacks and their fights for justice. Lastly was the holistic fights of the blacks for their rights became evident in the portrayal of the important figure to support the justice seeking. The series also highlighted the sustainable racial justice. In other words, the series had an intention to voice up the necessity of unity and mutual support in the society for preserving justice.